Method for preparing Au-coated Pt / C catalyst through continuous flow method and application of Au-coated Pt / C catalyst
By synthesizing Au@Pt nanoparticles in a continuous flow device and mixing them with activated carbon to form an Au@Pt/C catalyst, the problems of Au@Pt core-shell materials in the prior art in continuous production and reaction parameter control are solved, and the problem of Au@Pt core-shell materials in the prior art is realized. Highly efficient hydrogenation of furfural agents significantly improve catalytic efficiency and selectivity.
Patent Information
- Application Number
- CN202411645810.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-18
AI Technical Summary
The prior art is difficult to effectively prepare Au@Pt core-shell materials with high uniformity in terms of continuous production, batch repetition and precise control of reaction parameters, especially in the high proportion of by-products generated in furfural hydrogenation reaction, which affects catalysis. Efficiency and selectivity.
Au nanoparticles were synthesized in a continuous flow device by continuous flow method, and reduced on the surface of Au@Pt nanoparticles by controlling the concentration of sodium borohydride. Then Au@Pt nanoparticles were mixed with activated carbon, and Au was loaded by continuous flow method. @Pt/C catalyst.
The efficient preparation of Au@Pt/C catalyst was achieved, and the conversion and selectivity of furfuryl alcohol in furfural hydrogenation reaction was improved, and the catalytic efficiency was increased by more than 42% compared with the traditional method.
Smart Images

Figure CN119455938A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of preparing supported precious metal catalysts by a continuous flow method, and in particular to a method for preparing Au@Pt / C catalysts by a continuous flow method. Background Art
[0002] The continuous flow method for preparing catalysts is a novel technology in which the reaction takes place in a channel with an inner diameter of several millimeters. In chemical engineering, continuous flow equipment can provide unique control over key reaction parameters due to the small size of the reactor. Continuous flow reactors have many advantages, including high mass and heat transfer efficiency, precise control of reaction temperature, pressure and time, easier integration and automation, and improved reaction efficiency, thus attracting the attention of many researchers.
[0003] Generally, there are several methods for synthesizing Au@Pt core-shell materials, including chemical deposition, dealloying, electrodeposition, surface segregation, atomic layer deposition, and physical deposition. However, the above methods still face great challenges in continuous production, batch repetition, and precise control of reaction parameters. The continuous flow method has many advantages, including enhanced heat and mass transfer, rapid and adjustable mixing of precursor solutions, continuous flow production, and low reagent consumption throughout the optimization process. These characteristics have prompted a large number of researchers to explore the use of continuous flow-based devices to synthesize functional nanomaterials with higher uniformity on a large scale.
[0004] Furfuryl alcohol is an important biomass platform molecule and an important intermediate for the manufacture of lysine, ascorbic acid (vitamin C), plasticizers, dispersants and lubricants. Therefore, it is of great significance to study the efficient conversion of furfuryl alcohol. The selective catalytic hydrogenation of furfural into valuable furfuryl alcohol is one of the key ways to convert lignocellulose-based biomass into valuable fuels and fine chemicals. For many years, researchers have been focusing on how to increase the catalytic efficiency of furfural selective preparation of furfuryl alcohol by rationally designing catalysts. Pt-based catalysts have been widely studied by scholars in the catalytic hydrogenation of furfural due to their high catalytic activity. Catalysts based on Pt nanoparticles often generate more by-products during the hydrogenation of furfural. Doping and modifying Pt-based catalysts to make them have higher furfural selectivity is one of the effective means to solve this problem. In view of the above problems, it is imperative to develop new strategies and methods for preparing catalysts to improve the conversion efficiency and selectivity of target products. Summary of the invention
[0005] The object of the present invention is to provide a method for preparing Au@Pt / C core-shell catalyst by continuous flow with simple operation and high synthesis efficiency and its application. Au nanoparticles are synthesized by continuous flow method, Pt is reduced on the surface of Au nanoparticles by continuous flow device, Au@Pt nanoparticles are prepared, and Au@Pt nanoparticles and activated carbon slurry are mixed in the continuous flow device. In the preparation of Au@4ML-Pt / C, the concentration of reducing agent sodium borohydride is 0.055 mg / mL (when preparing Au nanoparticles) and 0.245 mg / mL (when preparing Au@Pt nanoparticles), which is the best, and can make the conversion rate of furfural hydrogenation to furfuryl alcohol as high as 72.2%, and the furfural selectivity is 71.0%, while the conversion rates of Pt / C catalyst prepared by continuous flow method and Pt / C catalyst prepared by catalyst and impregnation method are only 40.5% and 36.6%, and the furfuryl alcohol selectivity is 30.1% and 36.4%, respectively. In comparison, the catalyst prepared using this method improved the catalytic efficiency by more than 42%. In addition, the Au core-Pt shell structure also made an important contribution to the yield of furfuryl alcohol.
[0006] In order to solve the technical problem of the present invention, the proposed technical solution is: a method for preparing Au@Pt / C catalyst by continuous flow method comprises the following steps:
[0007] (1) Au nanoparticles are obtained by mixing chloroauric acid solution and sodium citrate aqueous solution with sodium borohydride aqueous solution in a continuous flow device; the mass ratio of Au to sodium borohydride is 1.2:1; the continuous flow preparation device is composed of a magnetic stirrer, a peristaltic pump, a collecting device and a Teflon pipe; the inlet pipe of the peristaltic pump is introduced into the container, the outlet pipe of the peristaltic pump is connected to a length of Teflon pipe, and finally the outlet end of the Teflon pipe is fixed above the collecting device; the collecting device is a beaker; the winding method of the Teflon pipe is circular;
[0008] (2) mixing the chloroplatinic acid solution with the Au nanoparticles in step (1) in a continuous flow device, and reducing them with a sodium borohydride aqueous solution to obtain Au@Pt nanoparticles; the mass ratio of Pt to sodium borohydride is 0.55:1;
[0009] (3) Adding activated carbon into deionized water and dispersing by stirring, and then subjecting to ultrasound to obtain activated carbon slurry;
[0010] (4) Using activated carbon as a carrier, the activated carbon slurry in step (3) is mixed with the Au@Pt nanoparticles in step (2) in a continuous flow device, and the obtained suspension is filtered and dried to prepare an Au@Pt / C catalyst.
[0011] Preferably, the Au@Pt / C is a 1wt% Au@4 ML-Pt / C catalyst, and the number of Pt shell atomic layers is 4.
[0012] Preferably, the Au@Pt / C is a 1wt% Au@4 ML-Pt / C catalyst, and the preparation steps are as follows:
[0013] The inner diameter of the Teflon tubing in the continuous flow device is 3 mm;
[0014] (1) Measure 100 mL of deionized water and place it in a beaker. Then take an appropriate amount of chloroauric acid to prepare a 0.05 mg / mL aqueous solution, add an appropriate amount of sodium citrate, and the mass ratio of Au to sodium citrate is 1:5. Stir at 1000 rpm for 1 min. Use a continuous flow device to prepare Au nanoparticles. Two pipes are fed with liquid. One pipe is fed with Au precursor aqueous solution, and the other pipe is fed with 100 mL of sodium borohydride aqueous solution with a concentration of 0.042 mg / mL prepared with ice water. The flow rate is 15 mL / min. After being converged by a three-way valve, Au nanoparticles are synthesized in a Teflon pipe. The time taken for the liquid to flow out from the pipe is 3 min. The prepared Au nanoparticles are stored in a refrigerator at 4°C.
[0015] (2) Au@Pt nanoparticles were prepared using a continuous-path device. The Au nanoparticle aqueous solution prepared in step (1) was introduced into one path at a flow rate of 5 mL / min. A 100 mL 0.15 mg / mL chloroplatinic acid aqueous solution was introduced into one path at a flow rate of 2.5 mL / min. The solution was converged through a three-way valve. The outflowing line was used as one liquid inlet. The other liquid inlet was 100 mL of 0.272 mg / mL sodium borohydride aqueous solution prepared with ice water. The flow rate of the peristaltic pump was 7.5 mL / min. The solution was converged through a three-way valve and reduced in a Teflon line. The time taken for the liquid to flow out from the line was 20 min. The prepared Au@Pt nanoparticles were collected in a beaker and waited for loading.
[0016] (3) Take 1980 mg of activated carbon in a beaker, add 500 mL of deionized water, stir at 1000 rpm for 1 min, and then ultrasonicate for 10 min to obtain activated carbon slurry;
[0017] (4) Using a continuous flow device to load Au@Pt onto activated carbon, two pipes were simultaneously fed with liquid at a flow rate of 25 mL / min, one pipe was fed with the Au@Pt nanoparticles prepared in step (2), and the other pipe was fed with the activated carbon slurry prepared in step (3). The two pipes were converged through a three-way valve, and the activated carbon slurry after loading was collected in a beaker;
[0018] (5) The catalyst slurry collected in step (4) was filtered and washed with deionized water until the conductivity was 0. The solid obtained after filtration was placed in a culture dish and dried in a vacuum drying oven at 80°C for 12 h. After drying, it was sealed and stored. The catalyst was named 1wt%Au@4ML-Pt / C.
[0019] In order to solve the technical problem of the present invention, another technical solution is proposed: the preparation method obtains Au@Pt / C catalyst.
[0020] In order to solve the technical problem of the present invention, another technical solution proposed is: the application of the Au@Pt / C catalyst, the Au@Pt / C catalyst is used for the reaction of hydrogenating furfural to prepare furfuryl alcohol.
[0021] Preferably, the prepared platinum-based catalyst is added to the reactor, the molar ratio of Pt to furfural in the catalyst is 1:1300, 1 mmol furfural, 8 mL isopropanol, and before the reaction, the reactor is purged with 1 MPa hydrogen for 3 times to remove the air in the reactor, and then filled with 1 MPa hydrogen, the reaction temperature is 50°C, the reaction time is 1 h, after the reaction is completed, the reactor is placed in ice water and quickly cooled to room temperature, the catalyst and the reaction liquid are separated, and the composition of the reaction liquid is detected by gas chromatography to obtain the reaction result.
[0022] Preferably, the platinum-based catalyst is 1wt% Au@4 ML-Pt / C, and the furfural is catalyzed by the catalyst 1wt% Au@4 ML-Pt / C to prepare furfural alcohol, with a furfural conversion rate of 72.2% and a furfural alcohol selectivity of 76.0%.
[0023] Beneficial effects of the present invention:
[0024] The present invention provides a continuous flow preparation method for an Au@Pt / C core-shell structure catalyst. The continuous flow device used can control the nucleation process of Au@Pt. The prepared particles have a small particle size, a narrow particle size distribution, and good dispersion, thereby avoiding human error problems such as operator techniques and easy mixing unevenness. The method is simple and efficient.
[0025] This method screened different amounts of reducing agent (sodium borohydride) added when preparing Au nanoparticles and Au@Pt nanoparticles, among which Example 4, in the preparation of Au@4 ML-Pt / C, the reducing agent sodium borohydride concentration was 0.055 mg / mL (when preparing Au nanoparticles) and 0.245 mg / mL (when preparing Au@Pt nanoparticles) for the best, which can make the conversion rate of furfural hydrogenation to furfuryl alcohol as high as 72.2%, and the furfural selectivity is 71.0%, while the conversion rates of Pt / C catalyst prepared by continuous flow method and Pt / C catalyst prepared by catalyst and impregnation method are only 40.5% and 36.6%, and the furfuryl alcohol selectivity is 30.1% and 36.4%, respectively. In contrast, the catalyst prepared by this method improves the catalytic efficiency by more than 42%, and the structure of Au core Pt shell also makes an important contribution to the yield of furfuryl alcohol.
[0026] The number of Pt shell atomic layers in the catalysts prepared in Examples 1-4 is 1 ML, 2 ML, 3 ML, and 4 ML, respectively. The catalyst prepared in Example 1 (1wt% Au@1 ML-Pt / C) has a furfural conversion rate of 71.9% and a furfuryl alcohol selectivity of 60.5%; the catalyst prepared in Example 2 (1wt% Au@2 ML-Pt / C) has a furfural conversion rate of 63.3% and a furfuryl alcohol selectivity of 64.2%; the catalyst prepared in Example 3 (1wt% Au@3 ML-Pt / C) has a furfural conversion rate of 62.7% and a furfuryl alcohol selectivity of 63.8%; the catalyst prepared in Example 4 (1wt% Au@4 ML-Pt / C) has a furfural conversion rate of 72.2% and a furfuryl alcohol selectivity of 76.0%. The catalysts prepared in Examples 1-4 have the best catalytic performance, and compared with Pt / C prepared by the impregnation method and the continuous flow method, the furfuryl alcohol yield has been increased by more than 42%. In addition, the activity and selectivity of the catalyst with Au core-Pt shell structure are better than those of Pt / C catalyst.
[0027] The catalyst prepared by this method is well dispersed and has no obvious agglomeration, while the platinum-based catalyst prepared by the impregnation method has obvious agglomeration and large differences in particle size. Mechanized operation can avoid human errors, make the results more repeatable, and greatly improve production efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 Schematic diagram of the continuous flow device
[0029] in Figure 1 : Peristaltic pump-1; Magnetic stirrer-2; Teflon tube-3;
[0030] Figure 2 TEM images of the Au@Pt catalysts prepared in Examples 1-4
[0031] Wherein a: Example 1; b: Example 2; c: Example 3; d: Example 4
[0032] Figure 3 TEM images of Au@Pt catalysts prepared in Comparative Examples 2-2, 2-4 and 2-5
[0033] Wherein a: Comparative Example 2-2; b: Comparative Example 2-4; c: Comparative Example 2-5
[0034] Figure 4 TEM image of Pt / C catalyst prepared by impregnation method
[0035] Figure 5 HAADF-STEM and EDS images of the Au@Pt / C catalyst prepared in Example 4
[0036] Figure 6UV-visible absorption spectrum of Au@Pt nanoparticles prepared in Example 4 DETAILED DESCRIPTION
[0037] The present invention is further described in detail below in conjunction with specific examples. These embodiments are only for illustrating the present invention, but the present invention is not limited to the following embodiments.
[0038] Example 1
[0039] The continuous flow preparation device is composed of a magnetic stirrer, a peristaltic pump, a collection device and a Teflon pipe. The inlet pipe of the peristaltic pump is introduced into the container, and the outlet pipe of the peristaltic pump is connected to a length of Teflon pipe. Finally, the outlet end of the Teflon pipe is fixed above the collection device. The collection device is a beaker, and the inner diameter of the Teflon pipe is 3 mm. The winding method of the Teflon pipe is circular.
[0040] (1) Measure 100 mL of deionized water and place it in a beaker. Then take an appropriate amount of chloroauric acid to make a 0.13 mg / mL aqueous solution, add an appropriate amount of sodium citrate (the mass ratio of Au to sodium citrate is 1:5), and stir at 1000 rpm for 1 min. Use a continuous flow device to prepare Au nanoparticles. Two pipes are fed with liquid. One pipe is fed with an Au precursor aqueous solution, and the other pipe is fed with 100 mL of a 0.108 mg / mL sodium borohydride aqueous solution prepared with ice water. The flow rate is 15 mL / min. After being converged by a three-way valve, Au nanoparticles are synthesized in a Teflon pipe. The time taken for the liquid to enter the pipe and flow out is about 3 minutes. The prepared Au nanoparticles can be stored in a refrigerator at 4°C.
[0041] (2) Au@Pt nanoparticles were prepared using a continuous-path device. The Au nanoparticle aqueous solution prepared in step (1) was introduced into one path at a flow rate of 5 mL / min. 100 mL of 0.07 mg / mL chloroplatinic acid aqueous solution was introduced into one path at a flow rate of 2.5 mL / min. The solution was converged through a three-way valve. The outflowing line was used as one liquid inlet. The other liquid inlet was 100 mL of 0.128 mg / mL sodium borohydride aqueous solution prepared with ice water. The peristaltic pump flow rate was 7.5 mL / min. The solution was converged through a three-way valve and reduced in a Teflon line. The time taken for the liquid to flow out from the line was 20 min. The prepared Au@Pt nanoparticles were collected in a beaker and waited for loading.
[0042] (3) Take 1980 mg of activated carbon in a beaker, add 500 mL of deionized water, stir at 1000 rpm for 1 min, and then ultrasonicate for 10 min to obtain activated carbon slurry.
[0043] (4) Au@Pt was loaded onto activated carbon using a continuous flow device. Two pipes were simultaneously fed with liquid at a flow rate of 25 mL / min. One pipe was fed with the Au@Pt nanoparticles prepared in step (2), and the other pipe was fed with the activated carbon slurry prepared in step (3). The two pipes were converged through a three-way valve and the loaded activated carbon slurry was collected in a beaker.
[0044] (5) The catalyst slurry collected in step (4) was filtered and washed with deionized water until the conductivity was 0. The solid obtained after the filtration was placed in a petri dish and dried in a vacuum drying oven at 80°C for 12 h. After the drying, it was sealed and stored.
[0045] The catalyst was named 1wt%Au@1 ML-Pt / C.
[0046] Example 2
[0047] The continuous flow preparation device is composed of a magnetic stirrer, a peristaltic pump, a collection device and a Teflon pipe. The inlet pipe of the peristaltic pump is introduced into the container, and the outlet pipe of the peristaltic pump is connected to a length of Teflon pipe. Finally, the outlet end of the Teflon pipe is fixed above the collection device. The collection device is a beaker, and the inner diameter of the Teflon pipe is 3 mm. The winding method of the Teflon pipe is circular.
[0048] (1) Measure 100 mL of deionized water and place it in a beaker. Then take an appropriate amount of chloroauric acid to make a 0.09 mg / mL aqueous solution, add an appropriate amount of sodium citrate (the mass ratio of Au to sodium citrate is 1:5), and stir at 1000 rpm for 1 min. Use a continuous flow device to prepare Au nanoparticles. Two pipes are fed with liquid. One pipe is fed with an Au precursor aqueous solution, and the other pipe is fed with 100 mL of a 0.075 mg / mL sodium borohydride aqueous solution prepared with ice water. The flow rate is 15 mL / min. After being converged by a three-way valve, Au nanoparticles are synthesized in a Teflon pipe. The time taken for the liquid to enter the pipe and flow out is about 3 minutes. The prepared Au nanoparticles can be stored in a refrigerator at 4°C.
[0049] (2) Au@Pt nanoparticles were prepared using a continuous-path device. The Au nanoparticle aqueous solution prepared in step (1) was introduced into one path at a flow rate of 5 mL / min. A 100 mL 0.11 mg / mL chloroplatinic acid aqueous solution was introduced into one path at a flow rate of 2.5 mL / min. The solution was converged through a three-way valve. The outflowing path was used as one liquid inlet. The other liquid inlet was 100 mL of 0.2 mg / mL sodium borohydride aqueous solution prepared with ice water. The peristaltic pump flow rate was 7.5 mL / min. The solution was converged through a three-way valve and reduced in a Teflon path. The time taken for the liquid to flow out from the path was 20 min. The prepared Au@Pt nanoparticles were collected in a beaker and waited for loading.
[0050] (3) Take 1980 mg of activated carbon in a beaker, add 500 mL of deionized water, stir at 1000 rpm for 1 min, and then ultrasonicate for 10 min to obtain activated carbon slurry.
[0051] (4) Au@Pt was loaded onto activated carbon using a continuous flow device. Two pipes were simultaneously fed with liquid at a flow rate of 25 mL / min. One pipe was fed with the Au@Pt nanoparticles prepared in step (2), and the other pipe was fed with the activated carbon slurry prepared in step (3). The two pipes were converged through a three-way valve and the loaded activated carbon slurry was collected in a beaker.
[0052] (5) The catalyst slurry collected in step (4) was filtered and washed with deionized water until the conductivity was 0. The solid obtained after the filtration was placed in a petri dish and dried in a vacuum drying oven at 80°C for 12 h. After the drying, it was sealed and stored.
[0053] The catalyst was named 1wt%Au@2 ML-Pt / C.
[0054] Comparative Example 2-1
[0055] The continuous flow preparation device is composed of a magnetic stirrer, a peristaltic pump, a collection device and a Teflon pipe. The inlet pipe of the peristaltic pump is introduced into the container, and the outlet pipe of the peristaltic pump is connected to a length of Teflon pipe. Finally, the outlet end of the Teflon pipe is fixed above the collection device. The collection device is a beaker, and the inner diameter of the Teflon pipe is 3 mm. The winding method of the Teflon pipe is circular.
[0056] (1) Measure 100 mL of deionized water and place it in a beaker. Then take an appropriate amount of chloroauric acid to make a 0.09 mg / mL aqueous solution, add an appropriate amount of sodium citrate (the mass ratio of Au to sodium citrate is 1:5), and stir at 1000 rpm for 1 min. Use a continuous flow device to prepare Au nanoparticles. Two pipes are fed with liquid. One pipe is fed with an Au precursor aqueous solution, and the other pipe is fed with 100 mL of a 0.075 mg / mL sodium borohydride aqueous solution prepared with ice water. The flow rate is 15 mL / min. After being converged by a three-way valve, Au nanoparticles are synthesized in a Teflon pipe. The time taken for the liquid to enter the pipe and flow out is about 3 minutes. The prepared Au nanoparticles can be stored in a refrigerator at 4°C.
[0057] (2) Au@Pt nanoparticles were prepared using a continuous-path device. The Au nanoparticle aqueous solution prepared in step (1) was introduced into one path at a flow rate of 5 mL / min. A 100 mL 0.11 mg / mL chloroplatinic acid aqueous solution was introduced into one path at a flow rate of 2.5 mL / min. The solution was converged through a three-way valve. The outflowing line was used as one liquid inlet. The other liquid inlet was 100 mL of 0.05 mg / mL sodium borohydride aqueous solution prepared with ice water. The peristaltic pump flow rate was 7.5 mL / min. The solution was converged through a three-way valve and reduced in a Teflon line. The time taken for the liquid to flow out from the line was 20 min. The prepared Au@Pt nanoparticles were collected in a beaker and waited for loading.
[0058] (3) Take 1980 mg of activated carbon in a beaker, add 500 mL of deionized water, stir at 1000 rpm for 1 min, and then ultrasonicate for 10 min to obtain activated carbon slurry.
[0059] (4) Au@Pt was loaded onto activated carbon using a continuous flow device. Two pipes were simultaneously fed with liquid at a flow rate of 25 mL / min. One pipe was fed with the Au@Pt nanoparticles prepared in step (2), and the other pipe was fed with the activated carbon slurry prepared in step (3). The two pipes were converged through a three-way valve and the loaded activated carbon slurry was collected in a beaker.
[0060] (5) The catalyst slurry collected in step (4) was filtered and washed with deionized water until the conductivity was 0. The solid obtained after the filtration was placed in a petri dish and dried in a vacuum drying oven at 80°C for 12 h. After the drying, it was sealed and stored.
[0061] The catalyst was named 1wt%Au@2 ML-Pt / C (m Pt :m NaBH4 =2.2:1).
[0062] Comparative Example 2-2
[0063] The continuous flow preparation device is composed of a magnetic stirrer, a peristaltic pump, a collection device and a Teflon pipe. The inlet pipe of the peristaltic pump is introduced into the container, and the outlet pipe of the peristaltic pump is connected to a length of Teflon pipe. Finally, the outlet end of the Teflon pipe is fixed above the collection device. The collection device is a beaker, and the inner diameter of the Teflon pipe is 3 mm. The winding method of the Teflon pipe is circular.
[0064] (1) Measure 100 mL of deionized water and place it in a beaker. Then take an appropriate amount of chloroauric acid to make a 0.09 mg / mL aqueous solution, add an appropriate amount of sodium citrate (the mass ratio of Au to sodium citrate is 1:5), and stir at 1000 rpm for 1 min. Use a continuous flow device to prepare Au nanoparticles. Two pipes are fed with liquid. One pipe is fed with an Au precursor aqueous solution, and the other pipe is fed with 100 mL of a 0.075 mg / mL sodium borohydride aqueous solution prepared with ice water. The flow rate is 15 mL / min. After being converged by a three-way valve, Au nanoparticles are synthesized in a Teflon pipe. The time taken for the liquid to enter the pipe and flow out is about 3 minutes. The prepared Au nanoparticles can be stored in a refrigerator at 4°C.
[0065] (2) Au@Pt nanoparticles were prepared using a continuous-path device. The Au nanoparticle aqueous solution prepared in step (1) was introduced into one path at a flow rate of 5 mL / min. A 100 mL 0.11 mg / mL chloroplatinic acid aqueous solution was introduced into one path at a flow rate of 2.5 mL / min. The solution was converged through a three-way valve. The outflowing line was used as one liquid inlet. The other liquid inlet was 100 mL of 0.4 mg / mL sodium borohydride aqueous solution prepared with ice water. The flow rate of the peristaltic pump was 7.5 mL / min. The solution was converged through a three-way valve and reduced in a Teflon line. The time taken for the liquid to flow out from the line was 20 min. The prepared Au@Pt nanoparticles were collected in a beaker and waited for loading.
[0066] (3) Take 1980 mg of activated carbon in a beaker, add 500 mL of deionized water, stir at 1000 rpm for 1 min, and then ultrasonicate for 10 min to obtain activated carbon slurry.
[0067] (4) Au@Pt was loaded onto activated carbon using a continuous flow device. Two pipes were simultaneously fed with liquid at a flow rate of 25 mL / min. One pipe was fed with the Au@Pt nanoparticles prepared in step (2), and the other pipe was fed with the activated carbon slurry prepared in step (3). The two pipes were converged through a three-way valve and the loaded activated carbon slurry was collected in a beaker.
[0068] (5) The catalyst slurry collected in step (4) was filtered and washed with deionized water until the conductivity was 0. The solid obtained after the filtration was placed in a petri dish and dried in a vacuum drying oven at 80°C for 12 h. After the drying, it was sealed and stored.
[0069] The catalyst was named 1wt%Au@2 ML-Pt / C (m Pt :m NaBH4 =0.275:1).
[0070] Comparative Examples 2-3
[0071] The continuous flow preparation device is composed of a magnetic stirrer, a peristaltic pump, a collection device and a Teflon pipe. The inlet pipe of the peristaltic pump is introduced into the container, and the outlet pipe of the peristaltic pump is connected to a length of Teflon pipe. Finally, the outlet end of the Teflon pipe is fixed above the collection device. The collection device is a beaker, and the inner diameter of the Teflon pipe is 3 mm. The winding method of the Teflon pipe is circular.
[0072] (1) Measure 100 mL of deionized water and place it in a beaker. Then take an appropriate amount of chloroauric acid to make a 0.09 mg / mL aqueous solution, add an appropriate amount of sodium citrate (the mass ratio of Au to sodium citrate is 1:5), and stir at 1000 rpm for 1 min. Use a continuous flow device to prepare Au nanoparticles. Two pipes are fed with liquid. One pipe is fed with an Au precursor aqueous solution, and the other pipe is fed with 100 mL of a 0.0375 mg / mL sodium borohydride aqueous solution prepared with ice water. The flow rate is 15 mL / min. After being converged by a three-way valve, Au nanoparticles are synthesized in a Teflon pipe. The time taken for the liquid to enter the pipe and flow out is about 3 minutes. The prepared Au nanoparticles can be stored in a refrigerator at 4°C.
[0073] (2) Au@Pt nanoparticles were prepared using a continuous-path device. The Au nanoparticle aqueous solution prepared in step (1) was introduced into one path at a flow rate of 5 mL / min. 100 mL of 0.11 mg / mL chloroplatinic acid aqueous solution was introduced into one path at a flow rate of 2.5 mL / min. The solution was converged through a three-way valve. The outflowing line was used as one liquid inlet. The other liquid inlet was 100 mL of 0.2 mg / mL sodium borohydride aqueous solution prepared with ice water. The peristaltic pump flow rate was 7.5 mL / min. The solution was converged through a three-way valve and reduced in a Teflon line. The time taken for the liquid to flow out from the line was 20 min. The prepared Au@Pt nanoparticles were collected in a beaker and waited for loading.
[0074] (3) Take 1980 mg of activated carbon in a beaker, add 500 mL of deionized water, stir at 1000 rpm for 1 min, and then ultrasonicate for 10 min to obtain activated carbon slurry.
[0075] (4) Au@Pt was loaded onto activated carbon using a continuous flow device. Two pipes were simultaneously fed with liquid at a flow rate of 25 mL / min. One pipe was fed with the Au@Pt nanoparticles prepared in step (2), and the other pipe was fed with the activated carbon slurry prepared in step (3). The two pipes were converged through a three-way valve and the loaded activated carbon slurry was collected in a beaker.
[0076] (5) The catalyst slurry collected in step (4) was filtered and washed with deionized water until the conductivity was 0. The solid obtained after the filtration was placed in a petri dish and dried in a vacuum drying oven at 80°C for 12 h. After the drying, it was sealed and stored.
[0077] The catalyst was named 1wt%Au@2 ML-Pt / C (m Au :m NaBH4 =2.4:1).
[0078] Comparative Examples 2-4
[0079] The continuous flow preparation device is composed of a magnetic stirrer, a peristaltic pump, a collection device and a Teflon pipe. The inlet pipe of the peristaltic pump is introduced into the container, and the outlet pipe of the peristaltic pump is connected to a length of Teflon pipe. Finally, the outlet end of the Teflon pipe is fixed above the collection device. The collection device is a beaker, and the inner diameter of the Teflon pipe is 3 mm. The winding method of the Teflon pipe is circular.
[0080] (1) Measure 100 mL of deionized water and place it in a beaker. Then take an appropriate amount of chloroauric acid to make a 0.09 mg / mL aqueous solution, add an appropriate amount of sodium citrate (the mass ratio of Au to sodium citrate is 1:5), and stir at 1000 rpm for 1 min. Use a continuous flow device to prepare Au nanoparticles. Two pipes are fed with liquid. One pipe is fed with an Au precursor aqueous solution, and the other pipe is fed with 100 mL of a 0.15 mg / mL sodium borohydride aqueous solution prepared with ice water. The flow rate is 15 mL / min. After being converged by a three-way valve, Au nanoparticles are synthesized in a Teflon pipe. The time taken for the liquid to enter the pipe and flow out is about 3 minutes. The prepared Au nanoparticles can be stored in a refrigerator at 4°C.
[0081] (2) Au@Pt nanoparticles were prepared using a continuous-path device. The Au nanoparticle aqueous solution prepared in step (1) was introduced into one path at a flow rate of 5 mL / min. 100 mL of 0.11 mg / mL chloroplatinic acid aqueous solution was introduced into one path at a flow rate of 2.5 mL / min. The solution was converged through a three-way valve. The outflowing line was used as one liquid inlet. The other liquid inlet was 100 mL of 0.2 mg / mL sodium borohydride aqueous solution prepared with ice water. The peristaltic pump flow rate was 7.5 mL / min. The solution was converged through a three-way valve and reduced in a Teflon line. The time taken for the liquid to flow out from the line was 20 min. The prepared Au@Pt nanoparticles were collected in a beaker and waited for loading.
[0082] (3) Take 1980 mg of activated carbon in a beaker, add 500 mL of deionized water, stir at 1000 rpm for 1 min, and then ultrasonicate for 10 min to obtain activated carbon slurry.
[0083] (4) Au@Pt was loaded onto activated carbon using a continuous flow device. Two pipes were simultaneously fed with liquid at a flow rate of 25 mL / min. One pipe was fed with the Au@Pt nanoparticles prepared in step (2), and the other pipe was fed with the activated carbon slurry prepared in step (3). The two pipes were converged through a three-way valve and the loaded activated carbon slurry was collected in a beaker.
[0084] (5) The catalyst slurry collected in step (4) was filtered and washed with deionized water until the conductivity was 0. The solid obtained after the filtration was placed in a petri dish and dried in a vacuum drying oven at 80°C for 12 h. After the drying, it was sealed and stored.
[0085] The catalyst was named 1wt%Au@2 ML-Pt / C (m Au :m NaBH4 =1.67:1).
[0086] Comparative Examples 2-5
[0087] (1) The continuous flow preparation device is composed of a magnetic stirrer, a peristaltic pump, a collection device and a Teflon tube. The inlet end of the peristaltic pump is introduced into the container, and the outlet end of the peristaltic pump is connected to a length of Teflon tube. Finally, the outlet end of the Teflon tube is fixed above the collection device. The collection device is a beaker, and the inner diameter of the Teflon tube is 3 mm. The winding method of the Teflon tube is circular.
[0088] (1) Measure 100 mL of deionized water and place it in a beaker. Then take an appropriate amount of chloroauric acid to make a 0.09 mg / mL aqueous solution, add an appropriate amount of sodium citrate (the mass ratio of Au to sodium citrate is 1:5), and stir at 1000 rpm for 1 min. Use a continuous flow device to prepare Au nanoparticles. Two pipes are fed with liquid. One pipe is fed with an Au precursor aqueous solution, and the other pipe is fed with 100 mL of a 0.3 mg / mL sodium borohydride aqueous solution prepared with ice water. The flow rate is 15 mL / min. After being converged by a three-way valve, Au nanoparticles are synthesized in a Teflon pipe. The time taken for the liquid to enter the pipe and flow out is about 3 minutes. The prepared Au nanoparticles can be stored in a refrigerator at 4°C.
[0089] (2) Au@Pt nanoparticles were prepared using a continuous-path device. The Au nanoparticle aqueous solution prepared in step (1) was introduced into one path at a flow rate of 5 mL / min. 100 mL of 0.11 mg / mL chloroplatinic acid aqueous solution was introduced into one path at a flow rate of 2.5 mL / min. The solution was converged through a three-way valve. The outflowing line was used as one liquid inlet. The other liquid inlet was 100 mL of 0.2 mg / mL sodium borohydride aqueous solution prepared with ice water. The flow rate of the peristaltic pump was 7.5 mL / min. The solution was converged through a three-way valve and reduced in a Teflon line. The time taken for the liquid to flow out from the line was 20 min. The prepared Au@Pt nanoparticles were collected in a beaker and waited for loading.
[0090] (3) Take 1980 mg of activated carbon in a beaker, add 500 mL of deionized water, stir at 1000 rpm for 1 min, and then ultrasonicate for 10 min to obtain activated carbon slurry.
[0091] (4) Au@Pt was loaded onto activated carbon using a continuous flow device. Two pipes were simultaneously fed with liquid at a flow rate of 25 mL / min. One pipe was fed with the Au@Pt nanoparticles prepared in step (2), and the other pipe was fed with the activated carbon slurry prepared in step (3). The two pipes were converged through a three-way valve and the loaded activated carbon slurry was collected in a beaker.
[0092] (5) The catalyst slurry collected in step (4) was filtered and washed with deionized water until the conductivity was 0. The solid obtained after the filtration was placed in a petri dish and dried in a vacuum drying oven at 80°C for 12 h. After the drying, it was sealed and stored.
[0093] The catalyst was named 1wt%Au@2 ML-Pt / C (m Au :m NaBH4 =1:0.3).
[0094] Example 3
[0095] The continuous flow preparation device is composed of a magnetic stirrer, a peristaltic pump, a collection device and a Teflon pipe. The inlet pipe of the peristaltic pump is introduced into the container, and the outlet pipe of the peristaltic pump is connected to a length of Teflon pipe. Finally, the outlet end of the Teflon pipe is fixed above the collection device. The collection device is a beaker, and the inner diameter of the Teflon pipe is 3 mm. The winding method of the Teflon pipe is circular.
[0096] (1) Measure 100 mL of deionized water and place it in a beaker. Then take an appropriate amount of chloroauric acid to make a 0.065 mg / mL aqueous solution, add an appropriate amount of sodium citrate (the mass ratio of Au to sodium citrate is 1:5), and stir at 1000 rpm for 1 min. Use a continuous flow device to prepare Au nanoparticles. Two pipes are fed with liquid. One pipe is fed with an Au precursor aqueous solution, and the other pipe is fed with 100 mL of a 0.055 mg / mL sodium borohydride aqueous solution prepared with ice water. The flow rate is 15 mL / min. After being converged by a three-way valve, Au nanoparticles are synthesized in a Teflon pipe. The time taken for the liquid to enter the pipe and flow out is about 3 minutes. The prepared Au nanoparticles can be stored in a refrigerator at 4°C.
[0097] (2) Au@Pt nanoparticles were prepared using a continuous-path device. The Au nanoparticle aqueous solution prepared in step (1) was introduced into one path at a flow rate of 5 mL / min. A 100 mL 0.135 mg / mL chloroplatinic acid aqueous solution was introduced into one path at a flow rate of 2.5 mL / min. The solution was converged through a three-way valve. The outflowing line was used as one liquid inlet. The other liquid inlet was 100 mL of 0.245 mg / mL sodium borohydride aqueous solution prepared with ice water. The peristaltic pump flow rate was 7.5 mL / min. The solution was converged through a three-way valve and reduced in a Teflon line. The time taken for the liquid to flow out from the line was 20 min. The prepared Au@Pt nanoparticles were collected in a beaker and waited for loading.
[0098] (3) Take 1980 mg of activated carbon in a beaker, add 500 mL of deionized water, stir at 1000 rpm for 1 min, and then ultrasonicate for 10 min to obtain activated carbon slurry.
[0099] (4) Au@Pt was loaded onto activated carbon using a continuous flow device. Two pipes were simultaneously fed with liquid at a flow rate of 25 mL / min. One pipe was fed with the Au@Pt nanoparticles prepared in step (2), and the other pipe was fed with the activated carbon slurry prepared in step (3). The two pipes were converged through a three-way valve and the loaded activated carbon slurry was collected in a beaker.
[0100] (5) The catalyst slurry collected in step (4) was filtered and washed with deionized water until the conductivity was 0. The solid obtained after the filtration was placed in a petri dish and dried in a vacuum drying oven at 80°C for 12 h. After the drying, it was sealed and stored.
[0101] The catalyst was named 1wt%Au@3 ML-Pt / C.
[0102] Example 4
[0103] The continuous flow preparation device is composed of a magnetic stirrer, a peristaltic pump, a collection device and a Teflon pipe. The inlet pipe of the peristaltic pump is introduced into the container, and the outlet pipe of the peristaltic pump is connected to a length of Teflon pipe. Finally, the outlet end of the Teflon pipe is fixed above the collection device. The collection device is a beaker, and the inner diameter of the Teflon pipe is 3 mm. The winding method of the Teflon pipe is circular.
[0104] (1) Measure 100 mL of deionized water and place it in a beaker. Then take an appropriate amount of chloroauric acid to make a 0.05 mg / mL aqueous solution, add an appropriate amount of sodium citrate (the mass ratio of Au to sodium citrate is 1:5), and stir at 1000 rpm for 1 min. Use a continuous flow device to prepare Au nanoparticles. Two pipes are fed with liquid. One pipe is fed with an Au precursor aqueous solution, and the other pipe is fed with 100 mL of a 0.042 mg / mL sodium borohydride aqueous solution prepared with ice water. The flow rate is 15 mL / min. After being converged by a three-way valve, Au nanoparticles are synthesized in a Teflon pipe. The time taken for the liquid to enter the pipe and flow out is about 3 minutes. The prepared Au nanoparticles can be stored in a refrigerator at 4°C.
[0105] (2) Au@Pt nanoparticles were prepared using a continuous-path device. The Au nanoparticle aqueous solution prepared in step (1) was introduced into one path at a flow rate of 5 mL / min. 100 mL of 0.15 mg / mL chloroplatinic acid aqueous solution was introduced into one path at a flow rate of 2.5 mL / min. The solution was converged through a three-way valve. The outflowing line was used as one liquid inlet. The other liquid inlet was 100 mL of 0.272 mg / mL sodium borohydride aqueous solution prepared with ice water. The peristaltic pump flow rate was 7.5 mL / min. The solution was converged through a three-way valve and reduced in a Teflon line. The time taken for the liquid to flow out from the line was 20 min. The prepared Au@Pt nanoparticles were collected in a beaker and waited for loading.
[0106] (3) Take 1980 mg of activated carbon in a beaker, add 500 mL of deionized water, stir at 1000 rpm for 1 min, and then ultrasonicate for 10 min to obtain activated carbon slurry.
[0107] (4) Au@Pt was loaded onto activated carbon using a continuous flow device. Two pipes were simultaneously fed with liquid at a flow rate of 25 mL / min. One pipe was fed with the Au@Pt nanoparticles prepared in step (2), and the other pipe was fed with the activated carbon slurry prepared in step (3). The two pipes were converged through a three-way valve and the loaded activated carbon slurry was collected in a beaker.
[0108] (5) The catalyst slurry collected in step (4) was filtered and washed with deionized water until the conductivity was 0. The solid obtained after the filtration was placed in a petri dish and dried in a vacuum drying oven at 80°C for 12 h. After the drying, it was sealed and stored.
[0109] The catalyst was named 1wt%Au@4 ML-Pt / C.
[0110] 1. Physical performance test
[0111] The catalysts prepared in Examples 1-4 and Comparative Examples 2-5 were weighed, dissolved in aqua regia, diluted to a fixed volume, and then tested by Inductively Coupled Plasma Optical Emission Spectrometer (ICP-OES). The results are shown in Table 1.
[0112] Table 1 Catalyst ICP-OES test results
[0113]
[0114] a The specific preparation method of continuous flow Pt / C catalyst is referenced in patent CN115850042B
[0115] b The specific preparation method of the impregnation Pt / C catalyst is referenced in patent CN113999088B
[0116] According to the above results, the loading rates of the catalysts prepared in Examples 1-4, Comparative Example 2-2, Comparative Example 2-4 and Comparative Example 2-5 are all greater than 95%, while the loading rates of the catalysts in Comparative Example 2-1 and Comparative Example 2-3 are less than 90% due to the low amount of sodium borohydride added, and the loading effect is poor.
[0117] The catalysts prepared in Examples 1-4, Comparative Examples 2-2, Comparative Examples 2-4 and Comparative Examples 2-5 were characterized by transmission electron microscopy (TEM). Figure 1 The particle size statistics are shown in Table 2.
[0118] Table 2 Particle size distribution of catalysts prepared in Examples 1-4, Comparative Examples 2-2, 2-4 and 2-5
[0119]
[0120] according to Figure 1According to the results in Table 2, the catalyst particles prepared in Examples 1-4 are small, with narrow particle size distribution, good dispersion, and good preparation effect. In Example 1-4, when synthesizing Au nanoparticles, the mass ratio of Au to sodium borohydride is 1.2:1, and when synthesizing Au@Pt nanoparticles, the mass ratio of Pt to sodium borohydride is 0.55:1, and the amount of reagent added is optimal. In Comparative Example 2-2, when synthesizing Au@Pt nanoparticles, the mass ratio of Pt to sodium borohydride is 0.275:1; in Comparative Examples 2-4 and 2-5, when synthesizing Au nanoparticles, the mass ratios of Au to sodium borohydride are 1.67:1 and 3.33:1, respectively. The above three comparative examples all have obvious agglomeration of particles due to excessive addition of sodium borohydride, and the preparation effect is not good.
[0121] according to Figure 5 , the nanostructure and element distribution of Au@4 ML-Pt / C catalyst were analyzed by HAADF-STEM. Figure 5 The HAADF-STEM image of the Au@4 ML-Pt / C catalyst and the EDS elemental mapping of Au (red) and Pt (green) are shown. From the EDS elemental mapping, the nanoparticles have a clear Au core-Pt shell structure, confirming the formation of the Au@Pt core-shell structure.
[0122] according to Figure 6 The UV-visible absorption spectrum shows that Au nanoparticles have an obvious absorption peak at 514 nm, while Pt nanoparticles have no obvious absorption peak in the range of 300-800 nm. However, Au@Pt nanoparticles have almost no absorption peak in the range of 300-800 nm, indicating that the surface of Au nanoparticles is covered by Pt, which indirectly proves the formation of Au@Pt core-shell structure.
[0123] Therefore, the catalysts prepared in Examples 1-4, the Pt / C catalysts prepared by the continuous flow method and the Pt / C catalysts prepared by the impregnation method can be used for the hydrogenation of furfural to prepare furfuryl alcohol.
[0124] 2. Test on the Reaction Activity of Furfural Hydrogenation to Furfuryl Alcohol
[0125] The reaction of furfural hydrogenation to prepare furfuryl alcohol was carried out in an autoclave equipped with a thermal conductivity detector. The prepared platinum-based catalyst (the molar ratio of Pt to furfural in the catalyst was 1:1300), 1 mmoL furfural, and 8 mL isopropanol were added to the reactor. Before the reaction, the reactor was purged with 1 MPa hydrogen for 3 times to remove the air in the reactor, and then filled with 1 MPa hydrogen. The reaction temperature was 50°C and the reaction time was 1 h. After the reaction was completed, the reactor was placed in ice water and quickly cooled to room temperature, the catalyst and the reaction liquid were separated, and the composition of the reaction liquid was detected by gas chromatography to obtain the reaction results. The test results are shown in Table 3.
[0126] Table 3 Reaction activity test of furfural hydrogenation to furfuryl alcohol
[0127]
[0128] The experimental results in Table 3 show the catalytic performance of catalysts with different Pt layer thicknesses in the reaction of furfural hydrogenation to furfuryl alcohol, and the superiority of the catalyst with Au core Pt shell structure compared with the Pt / C catalyst in the reaction. The difference between the catalysts prepared in Examples 1-4 is that the mass ratio of Au and Pt in the catalyst is different, that is, the atomic molar ratio of Au and Pt is different. By controlling the addition amount of Au and Pt, the thickness of the Pt shell in the Au@Pt nanoparticles can be controlled. The calculation method of the Pt shell thickness is shown in formula (1):
[0129]
[0130] Where y is the number of shells, ML is the thickness of the atomic layer (for example, 1 ML represents the thickness of 1 atomic layer), and d Au@Pt is the diameter of Au@Pt nanoparticles in TEM images, d Au is the diameter of Au nanoparticles in TEM images, d Pt is the Pt atomic diameter.
[0131] The particle size distribution of Au nanoparticles prepared in step (1) of Examples 1-4 is shown in Table 4.
[0132] Table 4 Particle size distribution of Au nanoparticles prepared in step (1) of Example 1-4
[0133]
[0134] Substituting the data in Table 2 and Table 4 into formula (1), it can be seen that the number of Pt shell atomic layers in the catalysts prepared in Examples 1-4 is 1 ML, 2 ML, 3 ML, and 4 ML, respectively. The catalyst prepared in Example 1 (1wt% Au@1 ML-Pt / C) has a furfural conversion rate of 71.9% and a furfural alcohol selectivity of 60.5%; the catalyst prepared in Example 2 (1wt% Au@2 ML-Pt / C) has a furfural conversion rate of 63.3% and a furfural alcohol selectivity of 64.2%; the catalyst prepared in Example 3 (1wt% Au@3 ML-Pt / C) has a furfural conversion rate of 62.7% and a furfural alcohol selectivity of 63.8%; the catalyst prepared in Example 4 (1wt% Au@4 ML-Pt / C) has a furfural conversion rate of 72.2% and a furfural alcohol selectivity of 76.0%. The catalyst prepared in Examples 1-4 has the best catalytic performance, and compared with Pt / C prepared by impregnation method and continuous flow method, the furfural alcohol yield has been improved by more than 42%. In addition, the activity and selectivity of the catalyst with Au core Pt shell structure are better than those of Pt / C catalyst.
[0135] It can be seen from the above examples that the present invention uses a continuous flow method to prepare an Au@Pt / C core-shell structure catalyst, and by optimizing the dosage of the reagents, a catalyst with high loading rate and good particle dispersion is obtained, which is applied to the reaction of furfural hydrogenation to prepare furfuryl alcohol.
[0136] The continuous flow device used in the present invention can control the nucleation process of Au@Pt, and the prepared particles have small particle size, narrow particle size distribution, and good dispersion.
[0137] And the prepared Au@Pt / C core-shell structure catalyst has good catalytic activity for furfural hydrogenation, and the yield of furfuryl alcohol is significantly improved. Compared with the previous process production route, the process route preparation process of the invention is simple, and the mechanized operation can effectively avoid human errors. The required catalyst can be obtained in one step, which greatly reduces the production time. The raw materials are renewable, the catalyst has high activity, the reaction conditions are mild, the energy consumption is reduced to a certain extent, it is environmentally friendly, and can effectively alleviate the energy problems facing the world today. Therefore, the present invention has broad application potential in industrial production.
[0138] The present invention is not limited to the specific technical solutions described in the above embodiments, and all technical solutions formed by equivalent replacement are within the protection scope required by the present invention.
Claims
1. A method for preparing Au@Pt / C catalyst by continuous flow method, characterized in that: The following steps are involved: (1) mixing a chloroauric acid solution with an aqueous sodium citrate solution and reducing it with an aqueous sodium borohydride solution in a continuous flow device to obtain Au nanoparticles; The mass ratio of Au to sodium borohydride is 1.2:1; the continuous flow preparation device is composed of a magnetic stirrer, a peristaltic pump, a collecting device and a Teflon pipe; the inlet pipe of the peristaltic pump is introduced into the container, the outlet pipe of the peristaltic pump is connected to a length of Teflon pipe, and finally the outlet end of the Teflon pipe is fixed above the collecting device; the collecting device is a beaker; the winding method of the Teflon pipe is circular; (2) mixing the chloroplatinic acid solution with the Au nanoparticles in step (1) in a continuous flow device, and reducing them with a sodium borohydride aqueous solution to obtain Au@Pt nanoparticles; the mass ratio of Pt to sodium borohydride is 0.55:1; (3) Adding activated carbon into deionized water and dispersing by stirring, and then subjecting to ultrasound to obtain activated carbon slurry; (4) Using activated carbon as a carrier, the activated carbon slurry in step (3) is mixed with the Au@Pt nanoparticles in step (2) in a continuous flow device, and the obtained suspension is filtered and dried to prepare an Au@Pt / C catalyst.
2. The method for preparing Au@Pt / C catalyst by continuous flow method according to claim 1, characterized in that: The Au@Pt / C is a 1wt% Au@4 ML-Pt / C catalyst, and the number of Pt shell atomic layers is 4.
3. The method for preparing Au@Pt / C catalyst by continuous flow method according to claim 2, characterized in that: The Au@Pt / C is a 1wt% Au@4 ML-Pt / C catalyst, and the preparation steps are as follows: The inner diameter of the Teflon tubing in the continuous flow device is 3 mm; (1) Measure 100 mL of deionized water and place it in a beaker. Then take an appropriate amount of chloroauric acid to prepare a 0.05 mg / mL aqueous solution, add an appropriate amount of sodium citrate, and the mass ratio of Au to sodium citrate is 1:
5. Stir at 1000 rpm for 1 min. Use a continuous flow device to prepare Au nanoparticles. Two pipes are fed with liquid. One pipe is fed with Au precursor aqueous solution, and the other pipe is fed with 100 mL of sodium borohydride aqueous solution with a concentration of 0.042 mg / mL prepared with ice water. The flow rate is 15 mL / min. After being converged by a three-way valve, Au nanoparticles are synthesized in a Teflon pipe. The time taken for the liquid to flow out from the pipe is 3 min. The prepared Au nanoparticles are stored in a refrigerator at 4°C. (2) Au@Pt nanoparticles were prepared using a continuous-path device. The Au nanoparticle aqueous solution prepared in step (1) was introduced into one path at a flow rate of 5 mL / min. A 100 mL 0.15 mg / mL chloroplatinic acid aqueous solution was introduced into one path at a flow rate of 2.5 mL / min. The solution was converged through a three-way valve. The outflowing pipeline was used as one liquid inlet. The other liquid inlet was 100 mL of 0.272 mg / mL sodium borohydride aqueous solution prepared with ice water. The peristaltic pump flow rate was 7.5 mL / min. The solution was converged through a three-way valve and reduced in a Teflon pipeline. The time taken for the liquid to flow out from the pipeline was 20 min. The prepared Au@Pt nanoparticles were collected in a beaker and waited for loading. (3) Take 1980 mg of activated carbon in a beaker, add 500 mL of deionized water, stir at 1000 rpm for 1 min, and then ultrasonicate for 10 min to obtain activated carbon slurry; (4) Using a continuous flow device to load Au@Pt onto activated carbon, two pipes were simultaneously fed with liquid at a flow rate of 25 mL / min, one pipe was fed with the Au@Pt nanoparticles prepared in step (2), and the other pipe was fed with the activated carbon slurry prepared in step (3). The two pipes were converged through a three-way valve, and the activated carbon slurry after loading was collected in a beaker; (5) The catalyst slurry collected in step (4) was filtered and washed with deionized water until the conductivity was 0. The solid obtained after filtration was placed in a culture dish and dried in a vacuum drying oven at 80°C for 12 h. After drying, it was sealed and stored. The catalyst was named 1wt%Au@4ML-Pt / C.
4. The Au@Pt / C catalyst is obtained according to any one of the preparation methods described in claims 1-3.
5. The use of the Au@Pt / C catalyst according to claim 4, characterized in that: Au@Pt / C catalyst was used for the hydrogenation of furfural to produce furfuryl alcohol.
6. The use of the Au@Pt / C catalyst according to claim 5, characterized in that: The prepared platinum-based catalyst was added to the reactor, the molar ratio of Pt to furfural in the catalyst was 1:1300, 1 mmol furfural, and 8 mL isopropanol. Before the reaction, the reactor was purged with 1 MPa hydrogen for 3 times to remove the air in the reactor, and then filled with 1 MPa hydrogen. The reaction temperature was 50°C and the reaction time was 1 h. After the reaction, the reactor was placed in ice water and quickly cooled to room temperature, the catalyst and the reaction liquid were separated, and the composition of the reaction liquid was detected by gas chromatography to obtain the reaction results.
7. The use of the Au@Pt / C catalyst according to claim 6, characterized in that: The platinum-based catalyst is 1wt% Au@4 ML-Pt / C. The catalyst 1wt% Au@4 ML-Pt / C is used to catalyze furfural to prepare furfural alcohol. The furfural conversion rate is 72.2% and the furfural alcohol selectivity is 76.0%.
Citation Information
Patent Citations
A method for the selective catalytic conversion of 2-methylfuran to 1,4-pentanediol
CN113999088B
Bimetallic catalyst for preparing furfuryl alcohol by furfural selective hydrogenation and preparation method and application thereof
CN110193370A
Preparation method and application of Pt-Au carbon-based in-situ reduction composite catalytic material
CN111468091A
Method for preparing ultralow-content gold-ruthenium bimetallic catalyst by using novel continuous flow technology
CN117983274A